(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This article wants to answer a very concrete question: what is the legal regime applicable to Software as Medical Device (SaMD)? This question is prompted by the fact that Medical Software can also embed an AI system and, if that is the case, it needs to be compliant as well with the newly approved AI Act (AIA) and not only with the Medical Devices Regulation (MDR). By using the principle of complementarity adopted by the AIA, I will give a first outline of what this new combined compliance might look like. The short answer is that it does not appear to be easy for SaMD manufacturers to understand how to integrate new and partly new elements within the older legislation, the MDR, which has the objectives of the AI Act.